Occupational Exposure to Organophosphate and Carbamate Pesticides Affects Sperm Chromatin Integrity and Reproductive Hormone Levels among Venezuelan Farm Workers. Issue 3 (4th October 2013) - Miranda‐Contreras, Leticia; Gómez‐Pérez, Roald; Rojas, Gerardo; Cruz, Ibis; Berrueta, Lisbeth; Salmen, Siham; Colmenares, Melisa; Barreto, Silvio; Balza, Alirio; Zavala, Leisalba; Morales, Yasmin; Molina, Yuri; et al.
Abstract : Occupational Exposure to Organophosphate and Carbamate Pesticides Affects Sperm Chromatin Integrity and Reproductive Hormone Levels among Venezuelan Farm Workers: Leticia MIRANDA‐CONTRERAS, et al . Electron Microscopy Center "Dr. Ernesto Palacios Prü", University of Los Andes, Venezuela— Objectives: Several reports suggest that chronic pesticide exposure may affect semen quality and male fertility in humans. The objective of this study was to evaluate the association between occupational exposure to organophosphate (OP) and carbamate (CB) pesticides and semen quality, as well as levels of reproductive and thyroid hormones of Venezuelan farm workers. Methods: Thirty‐five healthy men (unexposed group) and 64 male agricultural workers (exposed group) were recruited for clinical evaluation of fertility status. Fresh semen samples were evaluated for sperm quality and analyzed for DNA fragmentation index (DFI) by flow cytometry. Pesticide exposure was assessed by measuring erythrocyte acetylcholinesterase (AChE) and plasma butyrylcholinesterase (BuChE) with a Test‐mate ChE field kit. Serum levels of total testosterone (Tt), follicle‐stimulating hormone (FSH), luteinizing hormone (LH), prolactin (PRL), thyroid stimulating hormone (TSH) and free thyroxine (FT4) were analyzed using enzyme immunoassay kits. Results: Evidence of pesticide exposure was found in 87.5% of farmers based on AChE and BuChE inhibition. Significant increments were observed in sperm DFI with significant decreases in some semen parameters. DFI was negatively correlated with BuChE, sperm concentration, morphology and vitality in these workers. The levels of Tt, PRL, FT4 and TSH appeared to be normal; however, there was a tendency for increased LH and FSH levels in exposed workers. Conclusions: Our results confirm the potential impact of chronic occupational exposure to OP/CB pesticides on male reproductive function, which may cause damage to sperm chromatin, decrease semen quality and produce alterations in reproductive hormones, leading to adverse reproductive health outcomes.